2021
DOI: 10.3390/v13112217
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Type F Bovine Enterovirus from Clinical Cattle with Diarrhoea

Abstract: Recently, bovine enterovirus (BEV) has caused several respiratory and gastrointestinal diseases outbreaks in cattle. Monitoring the epidemiological and pathogenic characteristics of this virus is crucial to controlling its spread. We isolated a BEV strain with typical cytopathic effects from the faeces of cows with significant diarrhoeal symptoms in China and observed the viral particles within 20–30 nm through transmission electron microscopy. Then, we designated this strain as HB19-1 in this study. The multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The growth curve of the 10th passage virus shows that peak titer is reached at 30 hpi. By electron microscopy, the CHN-SCMY2021 particle is about 25 nm diameter which is consistent with the size of enterovirus particles ( Ji et al., 2021 ). Previous studies have shown that EV-G can be propagated in ST and Marc-145 cells ( Anbalagan et al., 2014 ; Mi et al., 2021 ; Shang et al., 2017 ).…”
Section: Discussionsupporting
confidence: 75%
“…The growth curve of the 10th passage virus shows that peak titer is reached at 30 hpi. By electron microscopy, the CHN-SCMY2021 particle is about 25 nm diameter which is consistent with the size of enterovirus particles ( Ji et al., 2021 ). Previous studies have shown that EV-G can be propagated in ST and Marc-145 cells ( Anbalagan et al., 2014 ; Mi et al., 2021 ; Shang et al., 2017 ).…”
Section: Discussionsupporting
confidence: 75%
“…We utilized lentivirus packaging of the plasmid constructs since preliminary experiments with MDBK cells (Institute of Cell Biology, Chinese Academy of Sciences, Shanghai, China) [ 13 ] had indicated that Lipofectamine 2000 (Invitrogen) transfection efficiencies were <5%. We therefore co-transfected 293T cells (Shanghai Biological Technology Co., Ltd. Enzymere, Shanghai, China) with the lentivirus packaging plasmid psPAX2 and lentiviral vector pMD2.G at 2:1:1) that were then incubated for 5 h according to the manufacturer’s specifications (Omega Bio-Tek, Dallas, Texas, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the genus of Enterovirus contains 12 species of enteroviruses (A-L) and 3 species of rhinoviruses (A, B, C) [ 16 ]. Out of 12 enterovirus species, enterovirus E (EV-E), enterovirus F (EV-F), and enterovirus G (EV-G) are mainly related to the infections affecting the livestock industry [ 17 , 18 , 19 , 20 ]. While enterovirus infections have been increasingly reported in cattle and pigs, they are still largely unknown in small ruminants such as sheep or goats.…”
Section: Introductionmentioning
confidence: 99%